SECONDARY SCHOOL STUDENTS' TYPES OF THINKING IN LEARNING MATHEMATICS - Reihenova, Austra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In this article author discusses different patterns of learners’ thinking learning mathematics. The main topic of this article is related to the different perceptions of each pupil, the ability to analyze and draw conclusions, therefore, the author proposes to change the organization of the study process and divide pupils into two groups, which will provide opportunities to acquire knowledge for each type of thinking in separate groups and at the appropriate pace and level. The aim of the article is to analyze the results of mathematical learning using different types of thinking and strategies. Student inspections, which were used as primary documents and questionnaires with open questions, were used to collect the data. The analysis of documents and the author's long-term work experience form the study. In the initial stage of the study, a case study analysis method was used for data processing.